(untitled) (Bangladesh Journal of Medical Science, 2026)
Background In low- and middle-income countries, smoking rates remain high while obesity is increasing due to poor diets rich in fat and sugar. Research has already linked smoking and high-fat diets to kidney injury, but we still don’t understand the specific mechanisms. Our research aims to explain the relationship between these lifestyle factors and microstructural kidney damage. Methods We used 24 male Wistar rats (200-250 grams) and split them into four groups: a control group, a high-fat diet (HFD) group, a cigarette smoke exposure (CSE) group, and a group receiving both treatments. After 28 days, we collected data on several health markers, including blood pressure, urea, and creatinine. We also measured the diameters of the glomerulus and the proximal convoluted tubule (PCT). To do this, we used plethysmography for blood pressure and H&E staining to examine the kidney tissue samples. Results The control group had an average weight of 232.2 grams and an SBP of 83.17 mmHg. In the HFD group, we saw a significant increase in both weight (280.5 grams) and SBP (193.2 mmHg) with p < 0.001. The rats in the HFD + CSE group reached the highest numbers, averaging 311.5 grams and an SBP of 202.5 mmHg (p < 0.001). Urea levels also rose sharply, from 9.46 mg/dl in the control group to 46.34 mg/dl in the combined HFD + CSE group (p < 0.001). For the kidney structure, the glomerular diameter increased from 201.46 μm to 315.58 μm, while the PCT lumen diameter shrank from 46.55 μm to only 17.41 μm (p < 0.001). Conclusions Our findings show that smoking and high-fat diets cause serious damage to kidney health. These results suggest that lifestyle changes are very important to prevent further injury. To protect the kidneys, it is essential for patients to stop smoking and improve their daily diet. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 797-805